Characteristics of Japanese elderly patients with pulmonary arterial hypertension. (September 2020) - Takahashi, Yukiko; Yamamoto, Keiko; Tanabe, Nobuhiro; Suda, Rika; Koshikawa, Ken; Ikubo, Yumiko; Suzuki, Eiko; Shoji, Hiroki; Naito, Akira; Kasai, Hajime; Nishimura, Rintaro; Sanada, Takayuki Jujo; et al.
Previous nationwide Japanese data suggested that pulmonary arterial hypertension (PAH) predominantly affects young women. However, the number of elderly patients diagnosed with PAH has been increasing in western countries. There have been no reports on elderly PAH patients in Asian countries. This study aimed to investigate the clinical characteristics of elderly PAH patients in a Japanese cohort. Idiopathic/heritable PAH (I/H-PAH) was included in the national research project on intractable diseases. The patients were required to submit a clinical research form completed by their attending physicians. We analyzed the characteristics of Japanese I/H-PAH using the newly registered forms in 2013 (Study 1, n = 148). Also, we did a retrospective, observational cohort study at Chiba University Hospital (Study 2, n = 42). We compared the characteristics of elderly PAH patients (≥65 years old) with younger patients (<65) in both studies. Study 1 revealed a predominance of males (51% male), better hemodynamics and poorer exercise capacity in the elderly group (n = 72), compared with the younger group (n = 76) in study 1. In Study 2, elderly patients showed a male predominance (63% male), a higher ratio of smokers, a lower % carbon monoxide diffusing capacity, and poorer exercise tolerance. Elderly patients in Study 2 showed less improvement in hemodynamics with therapy. There was no significant difference in disease-specific survival between elderly and younger patients. Japanese elderly patients with I/H-PAH showed poorer exercise capacity and impaired gas exchange, but better pulmonary hemodynamics than younger patients.